2007
DOI: 10.21273/hortsci.42.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Target Region Amplification Polymorphism (TRAP) as a Tool for Detecting Genetic Variation in the Genus Pelargonium

Abstract: Pelargonium was a priority genera collected by the Ornamental Plant Germplasm Center (OPGC) until a recent reorganization. To preserve genetic diversity for future breeders, OPGC collects heirloom cultivars, breeding lines, and wild species. The current Pelargonium collection at OPGC consists primarily of cultivars originating from P. ×hortorum and P. ×domesticum. Target region amplification pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In the rapid, efficient PCR-based TRAP marker system, expressed sequence tag database information and bioinformatics tools are used to generate polymorphic markers around targeted candidate gene sequences. Previous studies of lettuce (Lactuca sativa) [34], sugarcane (Saccharum officinarum) [35], spinach (Spinacia oleracea) [29], geranium (Pelargonium inquinans) [36], sunflower (Helianthus annuus) [37], and faba beans (Vicia faba) [16] have demonstrated that TRAP markers are useful for assessing genetic diversity. Using this system in the present study, we PCR-amplified 551 fragments with 16 primer combinations and observed considerable variation in the percentage of polymorphic amplicons among primer pairs-from 32.35% to 84.00% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the rapid, efficient PCR-based TRAP marker system, expressed sequence tag database information and bioinformatics tools are used to generate polymorphic markers around targeted candidate gene sequences. Previous studies of lettuce (Lactuca sativa) [34], sugarcane (Saccharum officinarum) [35], spinach (Spinacia oleracea) [29], geranium (Pelargonium inquinans) [36], sunflower (Helianthus annuus) [37], and faba beans (Vicia faba) [16] have demonstrated that TRAP markers are useful for assessing genetic diversity. Using this system in the present study, we PCR-amplified 551 fragments with 16 primer combinations and observed considerable variation in the percentage of polymorphic amplicons among primer pairs-from 32.35% to 84.00% (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…It uses a fixed primer of about 18 nucleotides, which is designed from the target-expressed sequence tag (EST) or gene sequence, as well as an arbitrary primer of about the same length, with either an AT or GC-rich core to anneal with an intron or exon, respectively (Hu and Vick 2003). As a simple yet powerful technique for estimating genetic diversity, TRAP has been successfully used for sugarcane, sunflower, Porphyra, Pelargonium, lettuce, and Spinacia oleracea germplasm diversity (Alwala et al 2006;Yue et al 2009;Qiao et al 2007;Palumbo et al 2007;Hu et al 2005;Hu et al 2007). Although TRAP has been introduced into fungi and proved to be reliable for analyzing genetic diversity of Lentinula edodes in China (Xiao et al 2010b), it was for the first time adopted in the present study for analyzing the diversity of A. auricula-judae.…”
Section: Introductionmentioning
confidence: 99%
“…TRAP uses a fixed primer designed against the known DNA gene sequence and pairs it with arbitrary primers that target the intron or exon regions with an AT-rich or GC-rich core (Li and Quiros, 2001) to amplify the DNA fragments. Published studies applying TRAP to lettuce (Hu et al , 2005), sugarcane (Alwala et al , 2006), Geranium (Palumbo et al , 2007), spinach (Hu et al , 2007) and sunflower (Yue et al , 2009) have suggested that TRAP is a useful marker system for germplasm diversity assessments. The objective of this study was to evaluate the usefulness of TRAP in revealing genetic diversity at both population and individual levels.…”
Section: Introductionmentioning
confidence: 99%